DIPG-68. ALPHA-THALASSEMIA X-LINKED MENTAL RETARDATION PROTEIN (ATRX) LOSS-OF-FUNCTION IN A MOUSE MODEL OF DIFFUSE INTRINSIC PONTINE GLIOMA. (4th December 2020) - Shen, Chen; Picketts, David; Becher, Oren
Abstract: Diffuse Intrinsic Potine Glioma (DIPG) is a rare pediatric brain tumor for which no cure or efficacious therapies exist. Previous discoveries have revealed that, DIPG harbors distinct genetic alterations, when compared with adult high-grade glioma (HGG) or even with non-DIPG pediatric HGGs. ATRX alteration is found in 9% of clinical cases of DIPG, and significantly overlaps with H3.3K27M mutation and p53 loss, the two most common genetic changes in DIPG, found in 80% and 77% clinical cases, respectively. Here we developed genetically engineered mouse model of brainstem glioma using the RCAS-Tv-a system by targeting PDGF-B overexpression, p53 loss, H3.3K27M mutation and ATRX loss-of function to Nestin-expression brainstem progenitor cells of the neonatal mouse. Specifically, we used Nestin-Tv-a; p53 floxed; ATRX heterozygous female and Nestin-Tv-a; p53 floxed; ATRX floxed male breeders, generated offsprings with ATRX loss of function (n=18), ATRX heterozygous females (n=6), and ATRX WT (n=10). Median survial of the three groups are 65 days, 88 days and 51 days, respectively. Also, ATRX null mice is lower in tumor incidence (44.4%), compared with ATRX WT (80%). We evaluated the pathological features of DIPG with or without ATRX alteration, RNA-seq is performed to identify differentially expressed genes between ATRX WT and loss-of-function. In conclution, this study generated the first genetically modified mouse model studying ATRX loss-of-function in DIPG, and suggested that ATRX loss-of-function in DIPG may slow down tumorigenesis and decrease tumor incidence.